Comparing Consumer Preferences for Livestock Production Process Attributes Across Products, Species, and Modeling Methods. (August 2014) - Widmar, Nicole J. Olynk; Ortega, David L.
Abstract : Consumer preferences for four livestock products were investigated to determine consumer willingness to pay (WTP) for livestock production process attributes. We use an inferred method of attribute nonattendance (ANA) using the coefficient of variation on individual specific parameter estimates to assess the variability of preference intensity for various product characteristics. We find that accounting for ANA did not significantly impact mean estimates of WT P. Implications of our findings on the reliability of existing work in the area of consumer preferences for animal welfare attributes are discussed.